SERVICE TEST OF SET, WELDING, EQUIPMENT: FOR NONFERROUS METALS, USED WITH 300 - AMPERE WELDING MACHINES - ARMY ARCTIC TEST CENTER FORT GREELY ALASKA (1961)
Service tests were made to determine if the welding set is suitable for Army use under arctic winter conditions at organizational maintenance level for welding nonferrous metals. The welding set is designed to adapt standard 300-amp enginedriven arc welding machines for inert-gas, metalarc welding. The test welder consists of an air-cooled hand gun with a self-contained wire drive and wire supply, a control monitor, a contactor, and an Ar gas regulator, all of whichARE INTERCONNECTED. The test welder is designed for semi-automatic welding of Al with filler wires from 0.040- to 3/64-in. diam, and is rated for continuous duty at 200 amp. Tests included (1) pre-operational inspection and physical characteristics, (2) compatibility with related equipment, (3) welding operations (3/8 to 3-in.thick Al alloy at 70 to -44F), (4) stowage and transportability, (5) maintenance, and (6) durability and reliability. On the basis of the tests, it was concluded that the welding set is suitable of Army use under arctic winter conditions at organizational maintenance level for welding nonferrous metals.